Correlation between chest x-ray findings and outcomes of patients with mechanical ventilation - Nurhayati, Indah; Supriatna, Muhammad; Raharjani, Kamilah Budhi; Sudijanto, Eddy (Paediatrica Indonesiana, 2013)
Background Most infants and children admitted to the pediatric intensive care unit (PICU) have respiratory distress and pulmonary disease as underlying conditions. Mechanical ventilation may be used to limit morbidity and mortality in children with respiratory failure. Objective To assess a correlation between chest x-ray findings and outcomes of patients with mechanical ventilation. Methods This retrospective study was held in Dr. Kariadi Hospital, Semarang, Indonesia. Data was collected from the medical records of children admitted to the PICU from January to December 2010, who suffered from respiratory distress and used mechanical ventilation. We compared chest x-ray findings to the outcomes of patients. Radiological expertise was provided by radiologists on duty at the time. Chi-square and logistic regression tests were used for statistical analysis. Results There were 63 subjects in our study, consisting of 28 males and 35 females. Patient outcomes were defined as survived or died, 43 subjects ( 68%) and 20 subjects (3 2%), respectively. Chest x-ray findings revealed the following conditions: bronchopneumonia 48% (P=0.298; 95%CI 0.22 to 1.88), pleural effusion 43% (P=0.280; 95%CI 0.539 to 4.837) , pulmonary edema 6% (P=0.622; 95%CI 0.14 to 14.62) and atelectasis 3% (P=0.538; 95%CI 0.03 to 7 .62). None of the chest x-ray findings significantly correlated to patient outcomes. Conclusion Chest x-ray findings do not correlate to patient outcomes in pediatric subjects with mechanical ventilation in the PICU of Dr. Kariadi Hospital, Semarang, Indonesia.